The impacts of ethical philosophy on the corporate hypocrisy perception and communication intentions toward CSR - SHIM, KyuJin (Institutional Knowledge at Singapore Management University, 2021)
This study investigates how perceptions of corporate hypocrisy from the Corporate Social Responsibility (CSR) activities connect the public’s ethical philosophy to subsequent positive/negative opinion-sharing intention. With special attention to deontology and consequentialism in normative ethics of philosophy, the current study empirically tests a theoretical model of perceived corporate hypocrisy with two causal antecedents (i.e., individual moral philosophy of deontology and consequentialism), and the mediating role of corporate hypocrisy between such antecedents and the publics’ subsequent communication intention (i.e., positive and negative opinion-sharing intentions) toward a firm. Results indicate significant mediation effects of corporate hypocrisy between personal ethical orientations and the public’s communication intention based on ethical attribution of crisis-related CSR activities.